Catalyst Technology Breakthroughs and Exploration of Fuel Cell Vehicle Commercialization Paths - Shi Peiji; Shen Rongwei; Wei Kaixin (E3S Web of Conferences)
Hydrogen fuel cell vehicles are regarded as an important direction for future transportation due to their zero emissions and high efficiency. Still, the high cost of high-platinum catalysts limits their commercialization. This article briefly describes the background of hydrogen fuel cell vehicles and emphasizes the key role of catalyst technology in improving performance and reducing costs. The research progress of low-platinum catalysts and non-precious metal catalysts is summarized, and their impact on efficiency, life, and system cost is analyzed. The challenges faced in the commercialization process are discussed, such as the contradiction between large-scale production and cost control, catalyst stability, and the lack of unified technical standards and global supply chain collaboration. It is proposed that comprehensive breakthroughs should be made in performance, cost, and large-scale production, and the linkage between technology and policy should be strengthened to accelerate the commercialization process. Finally, research directions that can be focused on in the future are proposed.